Beneath The Academic Pressure: Factors and Impacts of Burnout in Third Semester Student - Cahyadewi, Apriani Paramita; Salsabila, Hanum Ziyanah; Gifaradela, Akiko; Jaro'ah, Siti (Educational Psychology Journal, 2024)
The demands of various academic assignments, both individual and group assignments, in the transition period of the third semester can lead to academic burnout due to several factors. The aim of this research is to determine specific factors that trigger burnout in third semester students at Surabaya State University and the impact on students, including their physical, psychological and daily aspects. This research used a qualitative method with a phenomenological approach and a total of three participants aged 19 to 21 years. The data collection technique was carried out using semi-structured interview techniques and data validation was carried out through member checking. Data were analyzed using thematic analysis techniques. The study found two major themes, namely the factors that cause academic burnout and the impact of academic burnout. Factors causing burnout in the three participants were divided into two, namely situational factors which include workload, supervision, and community, as well as individual factors which include personality and individual behavior towards the responsibilities. Meanwhile, the impact of burnout includes psychological, physical and daily aspects. Active action is needed to overcome academic burnout experienced by students to improve psychological well-being in the campus environment.